Desarrollo de un filtro digital promedio en fpga - Melgarejo Rey, Miguel Alberto (Ingeniería, 1999)
This paper presents the modeling, design and probe of a FPGA-based digital average filter. PLD-based hardware implementation is recommended due to average filters use simple computational operations. The filter was used into a discrete time control system in order to reduce AWGN.